2022
DOI: 10.3390/ijms23147835
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Axis between Epithelial Splicing Regulatory Proteins and Estrogen Receptor α Modulates the Alternative Transcriptome of Luminal Breast Cancer

Abstract: Epithelial splicing regulatory proteins 1 and 2 (ESRP1/2) control the splicing pattern during epithelial to mesenchymal transition (EMT) in a physiological context and in cancer, including breast cancer (BC). Here, we report that ESRP1, but not ESRP2, is overexpressed in luminal BCs of patients with poor prognosis and correlates with estrogen receptor α (ERα) levels. Analysis of ERα genome-binding profiles in cell lines and primary breast tumors showed its binding in the proximity of ESRP1 and ESRP2 genes, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…TOP1 is a metalloendopeptidase, it hydrolyzes neuroendocrine and cardiovascular peptides [47], and may affect angiotensin converting enzyme II (ACEII) expression in alveolar epithelial cells and vascular endothelial cells that is associated with alveolar fluid clearance [47]. ESRP2 is an RNA binding proteins that controls splicing events during epithelial-mesenchymal transition [48] and is required for maintenance of epithelial cell barriers [49] and lung cell homeostasis [50]. IFT88, a subunit of proteins in the IFT machinery.…”
Section: Plos Onementioning
confidence: 99%
“…TOP1 is a metalloendopeptidase, it hydrolyzes neuroendocrine and cardiovascular peptides [47], and may affect angiotensin converting enzyme II (ACEII) expression in alveolar epithelial cells and vascular endothelial cells that is associated with alveolar fluid clearance [47]. ESRP2 is an RNA binding proteins that controls splicing events during epithelial-mesenchymal transition [48] and is required for maintenance of epithelial cell barriers [49] and lung cell homeostasis [50]. IFT88, a subunit of proteins in the IFT machinery.…”
Section: Plos Onementioning
confidence: 99%
“…Higher levels of ESRP1 expression have been detected in breast cancer, and have been associated with poor prognosis in oestrogen receptor positive breast cancer cells [54]. ESRP1 is controlled by the steroid hormone receptor ERα in breast cancer cells, and there are ERα binding sites within ESRP1 and ESRP2 promoters [55]. ESRP1 is also controlled by the transcription factor E2F1 in breast cancer cells and sensitive to oxygen levels [56].…”
Section: Could Esrp1 and Esrp2 Be Lineage Survival Oncogenes In Other...mentioning
confidence: 99%
“…In hormone-dependent cancers such as breast and prostate cancers, ESRP1 expression was shown to be associated with steroid hormone signaling. Public transcriptome and chromatin immunoprecipitation-sequencing data analyses revealed that ESRP1 expression correlates with ESR1 expression in breast cancer, and ERα binding sites are located within the ESRP1 promoter, suggesting that ESRP1 expression is regulated by ERα signaling in breast cancer [ 82 ]. Similarly, androgen levels were found to regulate ESRP1 expression.…”
Section: Esrp1 Regulation In Cancermentioning
confidence: 99%